Reformulation of Fintech Peer to Peer Landing Regulations: Critical Review of Predatory Pricing in the Implementation of Interest Rates - Handayani, Otih; Muryanto, Yudho Taruno; Masri, Esther (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Fintech Peer to Peer Lending (P2P Lending) have interest rates that tend to be higher and installment terms that are more concise than conventional loans. The Business Competition Supervisory Commission (KPPU) suspects that there is a cartel of agreements to determine interest rates by the Indonesian Joint Funding Fintech Association (AFPI) until finallyFinancial Services Authority (OJK) issued Financial Services Authority Circular (SEOJK) No. 19/SEOJK.06/2023 number VI which governregarding the maximum interest rate limit. This research aims to analyze the settingP2P Lending justice-based with a critical review of predatory pricing in the application of interest ratesP2P Lending. This research is doctrinal/normative legal research with a statutory approach. Literature study, analyzed qualitatively. The research results describe that SEOJK No. 19/SEOJK.06/2023 is actually a monopolistic practice by the government which unilaterally protects the Loan Recipient, this is contrary to economic democracy which requires equal opportunities for Lenders and Platforms to participate in encouraging economic growth and the functioning of a fair market economy due to the potential for predatory pricing which can cause Platforms to be unable to develop and even tend to experience business failure.